Genus Opithandra B. L. Burtt and Species Opithandra Dinghushanensis W. T. Wang as New Records for the Flora of Vietnam from Bac Huong Hoa Nature Reserve, Quang Tri Province - Xuyen, Do Thi; Phuong, Vu Xuan; Hoan, Ha Van; Duc, Nguyen Anh (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: A new record of genus and species as Opithandra B. L. Burtt and species Opithandra dinghushanensis W. T. Wang for the flora of Vietnam. This is herb, which was called endemic of China, but up to now we have found it in Bac Huong Hoa Nature Reserve (Quang Tri province). Voucher specimens were deposited in the Herbarium of the Hanoi University of Scicence, Vietnam (HNU). Keywords: Gesneriaceae, Opithandra, O. dinghushanensis, Bac Huong Hoa Nature Reserve, Quang Tri.